Efisiensi Kepemimpinan Pendidikan Dalam Optimalisasi Sumber Daya Sekolah - Adisty Zulfah Rizki Irani; Syahlaul Khaniyah; Sayyidah Alfi Nabila; Ahmad Sahrul Hamdani (CV. ITTC INDONESIA, 2024)
. The efficiency of educational leadership plays an important role in optimizing school resources to achieve quality education goals. This study aims to analyze the definition of effective and efficient leadership, the factors that affect the success of leaders in achieving goals, and the benefits of implementing efficient leadership, as well as effective leadership strategies in managing human and material resources in the school environment. The research method used is a qualitative approach with data collection techniques through literature studies. The results of the study show that leadership based on collaboration, transparency, and participatory decision-making has a significant impact on improving the efficiency of school resource management. In addition, the use of information and communication technology (ICT) has been proven to accelerate the administrative process and the appropriate allocation of resources. The study concludes that educational leaders who are able to integrate innovation and adaptive managerial approaches can improve school operational effectiveness while creating a productive learning environment